Application development with Microsoft Access - Balter, Alison; Safari eBooks ([Indianapolis?] : Sams, 2008)
"This course brings together more than twelve hours of personalized, expert video training: 100+ quick, practical video lessons that demonstrate all the skills you need to build virtually any Access application. You'll learn one step at a time, at your own pace-using hands-on examples that reflect realistic development challenges and showcase Access 2007's remarkable capabilities."--Resource description page.
System requirements: Adobe Flash Player, version 8 or higher; or QuickTime Player, version 7.2 or higher; or Windows Media Player, version 11 or higher.
Title from resource description page (viewed Jan. 14, 2009).
Electronic reproduction.
Keywords: Microsoft Access; Database management; Electronic books